Art Deco Jewelry in France: Interaction between Culture and Accessories in the 1920’s ‒ 1930’s - Krasnokutskaya, Maria A. (Actual Problems of Theory and History of Art, 2013)
The article is dedicated to a problem of interaction between the main artistic trends and jewelry in France in the 1920’s and 30’s. Special attention is paid to Art deco jewelry in the context of cultural and artistic life of the period.
Keywords: France; Art deco; jewelry; modernism